Severe maternal hardships are associated with food insecurity among low-income/lower-income women during pregnancy: results from the 2012-2014 California maternal infant health assessment - Barbara A. Laraia; Ryan Gamba; Carina Saraiva; Melanie S. Dove; Kristen Marchi; Paula Braveman (BMC, 2022)
Abstract Background Assess the associations between ten severe maternal hardships and food insecurity experienced during pregnancy. Methods Data on 14,274 low-income/lower-income women (below 400% of the income to federal poverty guideline ratio) from the statewide-representative 2010-2012 California Maternal and Infant Health Assessment were used to estimate food security status prevalence. Prevalence of severe maternal hardships by food security status was estimated. Multinomial logistic regression was used to assess the associations between severe maternal hardship and food security status, adjusting for sociodemographic characteristics. Results Food insecurity was common among low- and lower-income pregnant women in California; 23.4% food insecure and an additional 11.5% marginally secure. In adjusted analysis, nine of ten hardships were associated with food security status. Only the respondent or someone close to the respondent having a problem with alcohol or drugs was not associated with food security status after adjusting for socioeconomic factors. Husband/partner losing a job, depressive symptoms, not having practical support and intimate partner violence were consistently associated with marginal, low and very low food security status. Each additional severe maternal hardship a woman experienced during pregnancy was associated with a 36% greater risk of reporting marginal food security (Relative Risk Ratio 1.36, 95% CI: 1.27, 1.47), 54% for low food security (Relative Risk Ratio 1.54, 95% CI: 1.44, 1.64), and 99% for very low food security (Relative Risk Ratio 1.99, 95% CI: 1.83, 2.15). Conclusions Food security status was strongly linked with several maternal hardships that could jeopardize maternal and/or infant health. Services-including prenatal care and nutritional assistance-for a large proportion of pregnant women should address a wide range of serious unmet social needs including food insecurity.